Penentuan Arahan dan Lokasi Rawan Kriminalitas di Kecamatan Panakkukang, Kota Makassar - Eizal Azis Edison; Arifuddin Akil; Abdul Rachman Rasyid (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2019)
Makassar City is the least livable city in the 2017 Most Liveable City Indonesia assessment by IAP with the lowest security aspect aspect and the second lowest security aspect and the number of crime rates in Makassar City has continued to increase in the last three years. Panakkukang District is the highest in the last three years. This study aims to determine the location of crime-prone, spatial factors associated with the selection of crime locations, spatial direction to reduce crime rates in Panakkukang District. The crimes referred to in this study are theft of houses, mugging, and stabbing with weapons / fire. Determination of crime-prone locations using kernel density analysis in ArcGIS applications. To determine the relationship of spatial factors associated with the selection of crime locations, Chi-Square analysis was used. The spatial factors in question are the spatial patterns of settlements, accessibility, and distribution of security facilities, economic facilities, and social facilities. In determining the spatial direction to reduce crime rates using analytical hierarchy process (AHP) and descriptive analysis. The results showed that there is a very crime-prone location in Panakkukang District. Related spatial factors are settlement spatial patterns, accessibility, government facilities. Spatial directives to reduce crime are restrictions on access by fencing walls or portals, guard posts for each access, providing security facilities in accordance with SNI 03-1733-2004, increasing supervision and lighting.